Exploring Genius Hour: A literature study on concepts, benefits, and their application at every level of education in various countries - Dhifa Putra Ramadhan; Dedi Kuswandi; Yerry Soepriyanto (Jurnal Inovasi Teknologi Pendidikan, 2023)
Genius Hour in this article will be studied in the literature, focusing on the concept and benefits of Genius Hour in the context of Education, as well as how Genius Hour is implemented in various countries at different levels of Education. It is hoped that the results of this study can provide further knowledge about Genius Hour and an overview for students who wish to apply to Genius Hour. Genius Hour is an approach to learning by setting aside time in class so students can learn about topics that match their interests or passions, developing essential questions, researching their topics, and creating a final project to be shared at the end of learning. The literature review in this study uses prism flow diagrams to assist in the process of determining the literature to be studied.Â